2023
DOI: 10.1080/07853890.2023.2256656
|View full text |Cite
|
Sign up to set email alerts
|

Health science staff and student experiences of teaching and assessing clinical skills using digital tools: a qualitative study

Annie O’Brien,
Cuisle Forde

Abstract: Introduction Once considered a supplement to traditional teaching approaches, digital tools now play a pivotal role in building core clinical competencies. This study aims to explore staff and student experiences of navigating the challenges of teaching and assessing clinical skills using digital technology. It also aims to provide insight into what skills, or aspects of skills, may be best suited to digitally enhanced teaching, thereby advancing the future of health science education. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Meta-analyses and qualitative research has found that technology successfully supports the acquisition of low-stake skills [ 9 , 14 ]. Skills requiring haptic awareness, manual dexterity and auditory training may however require in-person practice and feedback to consolidate [ 15 ]. A systematic review has determined that many studies of digital medical education are low-quality [ 16 ]; reviews predominantly compare digitally enhanced teaching against one other teaching approach, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analyses and qualitative research has found that technology successfully supports the acquisition of low-stake skills [ 9 , 14 ]. Skills requiring haptic awareness, manual dexterity and auditory training may however require in-person practice and feedback to consolidate [ 15 ]. A systematic review has determined that many studies of digital medical education are low-quality [ 16 ]; reviews predominantly compare digitally enhanced teaching against one other teaching approach, i.e.…”
Section: Introductionmentioning
confidence: 99%